Behavioral Approach Through Assertive Training in Improving Interpersonal Communication Skills of Students: A Systematic Literature Review - Nuha, Moch. Syihabudin; Hidayah, Nur; Wahyuni, Fitri (Indonesian Journal of Educational Counseling, 2024)
First-year students encounter new and latest things that they might not have gotten before entering college. One of the main concerns is interpersonal communication skills, which are either mandatory or simply necessary for them to know in order to communicate in the campus environment. Interpersonal skills have many benefits, including making them more confident, able to speak in public, accepting of themselves, and able to build healthy relationships with others. Various types of bullying that occur in the environments of students and college students are influenced by many factors, including low self-acceptance. This can make them less accepting of themselves, unable to accept rejection or criticism, and even closed off to others. Therefore, the researcher wanted to find literature sources related to how to improve interpersonal communication skills through assertive training in 2023. The method used was systematic literature review (SLR). The results show that assertive training for students can improve interpersonal communication skills.